Hydrogen Controls the Heavy Atom Roaming in Transient Negative Ion - Pataraprasitpon, Smith; Luxford, Thomas F M; Čurík, Roman; Kočišek, Jaroslav; Piekarski, Dariusz G (Journal of the American Chemical Society, 2025)
Bromine and hydrogen play unusual roles as mobile atom and dissociation dynamics moderator, respectively, during roaming in the 3-bromo-4H-1,2,4-triazole anion. The present study of the reactivity of 3-bromo-1H-1,2,4-triazole and 3-bromo-4H-1,2,4-triazole with low-energy electrons reveals the effect of the hydrogen position on the reaction dynamics. We report energy-dependent ion yields for both molecules showing significant differences. Quantum chemical calculations reveal that heavy Br atom migration is energetically more favored than H atom migration in the case of the H atom adjacent to Br. This is enabled by the energetically favorable formation of a noncovalent complex of Br- around the triazole ring. Recently, such complexes have been reported for several other biologically relevant molecules. In the present work, we demonstrate that the position of hydrogen on the ring influences the character of the lowest resonant state and, consequently, the Br- roaming and dissociation dynamics, particularly the neutral release of hydrogen bromide.